Groups whose all infinite Abelian pd-subgroups are normal - Liman , F. N. (Ukrains’kyi Matematychnyi Zhurnal, 1992)
The author studies groups in which any infinite Abelian pd-subgroup (p is a prime) is normal, on the assumption that the group indeed contains such subgroups (IНр-groups). Necessary and sufficient conditions are established for a group to be an IНр-group. Relationships are established between the class of IНр-groups and the class of groups in which all infinite Abelian subgroups are normal, and the class of groups in which all pd-subgroups are normal.